Stars, Seasons, and Spirituality: the Astronomical Roots of Ethiopian New Year Celebrations - Belay Sitotaw Goshu; Melaku Masresha Woldemariam (Britain International for Academic Research (BIAR) Publisher, 2024)
This study looks at the astronomical and cultural significance of the New Year's festivities of six ethnic groups in Ethiopia: the Oromo, Sidama, Gurage, Welayeta, Amhara, and Tigray peoples. In September, each group observes the Ethiopian New Year by the Enkutatash celebration, which is based on traditional practices and the Ethiopian solar calendar. The study examines the effects of astronomical phenomena, such as moon phases and the solar cycle, on the timekeeping practices and New Year's festivities of these diverse cultures. Based on the biblical tale of Noah's dove, which stands for hope and renewal, the study emphasizes themes of regeneration and the need for new beginnings. Customs such as the Oromo Waqeffanna, Welayeta Gifata celebration, and the Amhara and Tigray peoples, demonstrate the relationship between astronomical observations, agricultural cycles, and cultural rites. The study also explores the Yewa Sureke celebration, which the Zeyise people of southern Ethiopia observe to commemorate the start of the agricultural year on a lunar calendar. The festival, which incorporates feasting, music, and rites of reverence for ancestors to fortify cultural identity, represents the resuscitation of spiritual and communal relationships. Finally, these results show how New Year's festivities preserve cultural continuity, foster social cohesiveness, and link contemporary customs to astronomical and historical contexts.